Optimizing Coconut Shell Waste for Biobriquettes as an Environmentally Friendly Energy Solution in Katapiang, Batang Anai, Padang Pariaman - Riski Gunawan Nasution; Rehan Aditya Nugraha; Aldo Firmansyah; Ryoshi Meijisa Reigi Putra; Alfi Syahri (Faculty of Engineering UNHAS, 2026)
This community service program aimed to optimize the utilization of coconut shell waste into biobriquettes as an environmentally friendly alternative energy source in Korong Pilubang, Nagari Katapiang. The program partners included farmer groups, PKK women's groups, youth organizations (Karang Taruna), and local MSMEs. This initiative addressed the issue of abundant coconut shell waste generated from coconut farming activities, which had not been optimally utilized and often contributed to environmental pollution. Through a participatory approach, the program provided comprehensive training and direct technical assistance covering carbonization, molding, and packaging processes of biobriquettes. The implementation produced biobriquettes with specifications of 3 cm in diameter, 6 cm in height, and a burning duration of 2–3 hours per unit. Quantitative evaluation using pre-test and post-test methods revealed significant improvements in participants' understanding of biobriquette concepts (from 45% to 85%), carbonization techniques (from 35% to 80%), economic benefits (from 50% to 90%), and practical skills (from 30% to 75%). The program has also generated measurable economic impact, including fuel cost savings of up to 40% for small businesses and 30% for households. These outcomes have been sustained through the establishment of an independent production group and increased community awareness of renewable energy and sustainable waste management, supported by close collaboration with the local village government.